Increased risk of placental abruption after solomon laser treatment of twin-twin transfusion syndrome. (May 2017) - Lanna, M.M.; Faiola, S.; Consonni, D.; Rustico, M.A.
Abstract: To evaluate the relative risk of placental abruption in monochorionic (MC) twin pregnancies complicated with twin-to-twin transfusion syndrome (TTTS) and treated with endoscopic laser coagulation of placental vessels (ELCPV). A retrospective analysis from January 2004 and December 2015 of 373 TTTS pregnancies, treated with selective ELCPV until January 2012 (287 cases), after which the Solomon technique was introduced (86 cases), compared with 243 normal MC pregnancies. A significant improvement in perinatal survival was observed after the introduction of the Solomon technique when compared to the selective procedure (77% vs 54%, p < 0.001). The rate of placental abruption was 1% (3/243) in normal MC pregnancies, 6% (21/373) in TTTS group, increased with Solomon technique (12/86, 14%, vs 9/287, 3%, p < 0.001). MC twin pregnancies treated with laser coagulation of placental vascular anastomoses could be at increased risk of placental abruption, especially when the Solomon technique is used. Highlights: There is a risk of placental abruption in TTTS pregnancies treated with fetoscopic laser coagulation of placental vessels. Solomon technique may be increasing the risk of placental abruption. Histological studies on monochorionic placentas treated with Solomon laser for TTTS could confirm these data.